POLYCHROMATIC PARADIGMS: THE SEMIOTICS OF COLOUR IN TAMIL CINEMATIC NARRATIVES - Amaljith N. K.; Shemin K.; Ameer Salman O. M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Colour plays an essential role in the visual narrative of Tamil cinema, not only enhancing the aesthetic appeal but also acting as a symbolic tool that conveys deeper emotional, cultural, and thematic meanings. Rooted in Tamil Nadu’s rich cultural traditions, the colours used in Tamil films often carry symbolic meanings derived from religion, folklore, and socio-political themes. This research paper explores the application of colour theory in Tamil cinema, examining how directors employ colour to evoke emotions, highlight socio-political contexts, and reflect cultural values unique to Tamil audiences. By studying specific colours and their repeated motifs across films, this paper investigates how Tamil cinema translates cultural symbolism into visual narratives that resonate deeply with audiences. Through case studies of iconic Tamil films such as Alaipayuthey, Paruthiveeran, Super Deluxe, Kaaka Muttai, Vada Chennai and Asuran, this paper decodes the language of colour in Tamil cinema, highlighting how directors like Mani Ratnam, Ameer Sultan, Thiagarajan Kumararaja and Vetrimaaran use colour palettes not only to define characters but also to convey underlying social commentary. The paper further explores the impact of digital technology in transforming colour grading and its effect on the stylistic choices available to filmmakers. By analyzing these films and colour usage, this study provides insights into how Tamil cinema integrates traditional cultural cues with modern filmmaking techniques, offering a visual language that enhances narrative depth and audience engagement.